Weak Form Efficiency of the Insurance Industry: Empirical Evidence from Nigeria - Emenike Kalu Onwukwe; Peter Ifeanyichukwu Ali (University of Merdeka Malang, 2018)
This paper evaluates the insurance sector of the Nigeria Stock Exchange (NSE) for evidence weak-form efficiency using daily returns from January 2009 to February 2016. The study employs descriptive analysis, non-parametric runs test and autocorrelation function as well as Ljung-Box Q statistics in conducting the evaluation. Descriptive statistics of the insurance sector return series show negative skewness and leptokurtic distribution. Estimates from the Jarque-Bera normality test show that the insurance sector returns do not follow a normal distribution. Results of the runs test reject a null hypothesis of randomness in the return series of the insurance sector in the period studied. Furthermore, the autocorrelation functions and the Ljung-Box Q tests provide evidence of serial correlation in the stock returns of the insurance sector. Overall results from the study suggest that the insurance sector of NSE is not weak-form efficient. Consequently, technical analysis on the insurance sector of the NSE may not be fruitless. JEL Classification: G14, G22DOI: https://doi.org/10.26905/jkdp.v22i1.1800